Case Report: The Coronal Magnetic Resonance Imaging of Three-Dimensional Fast-Field Echo With Water-Selective Excitation Can Identify the Wrapping of Spinal Nerve Fibers Into Subdural Tumors Prior to Operation - Tang, Tao; Yuan, Jinghong; Yin, Jianhua; Zhu, Junchao; Jia, Jingyu; Cheng, Xigao (Frontiers in Neurology, 2022)
Purpose: In present study, the authors intend to identify the spatial relationship between subdural tumors and spinal nerve fibers of cauda equina prior to operation using the coronal magnetic resonance imaging of three-dimensional fast-field echo with water-selective excitation (CMRI). Methods: Thirty series cases with surgically and pathologically verified subdural tumors were enrolled in present study. The spatial relationship between subdural tumors and spinal nerve fibers of cauda equina was assessed via conventional MRI and CMRI by three experts prior to operation. The spatial relationship between subdural tumors and spinal nerve fibers of cauda equina was classified using CMRI. Accuracy of imaging observation was determined via intraoperative observation. Results: Though conventional MRI and Gd MRI cannot identify the spatial relationship between subdural tumors and spinal nerve fibers of cauda equina in all cases, CMRI can identify it prior to operation and divide the spatial relationship of spinal nerve fibers of cauda equina with subdural tumors into three types. CMRI shows higher sensitivity (97.44%) and specificity (90.47%) in identifying the spatial relationship of spinal nerve fibers of cauda equina with subdural tumors. Additionally, CMRI also showed a substantial agreement with a kappa value of 0.78. Conclusion: Herein, the authors first describe a potential novel application that CMRI can successfully identify the spatial relationship between subdural tumors and spinal nerve fibers of cauda equina prior to operation, which play an essential role on making a prudent surgical plan and preventing postoperative nerve damage. Summary: Intraoperative observation confirms spinal nerve fibers of cauda equina often are wrapped into subdural tumors of thoracolumbar and lumbar region, which can result in a high rate of sensory and motor dysfunction after the operation due to the unconscious about the wrapping of nerve into subdural tumors prior to operation. To date, there is not an effective strategy to identify the wrapping before operation.